Pengaruh IPK, Micro Teaching, dan Praktik Pengalaman Lapangan (PPL) terhadap Kompetensi Pedagogik Mahasiswa Calon Guru Jurusan Pendidikan Ekonomi FE UNP - Mardiah Mardiah; Yulhendri Yulhendri (Universitas Negeri Padang, 2020)
This study aims to identify and analyze the influence of the average average value, micro teaching, and field experience (PFE) on pedagogical competencies of prospective teachers majoring in economic education at Padang State University. The population in this study were students majoring in economic education in 2015 at Padang State University. The analytical method used is multiple regression analysis using SPSS version 21. The results show that 1) The average point value does not significantly influence the pedagogical competence of prospective teacher students majoring in economic education at Padang State University 2) Micro teaching has a significant effect on the pedagogical competency of the candidates student teacher majoring in economic education majoring in Padang State University 3) Practice Field experience (pfe) does not have a significant effect on pedagogical competence of prospective teacher students majoring in economic education at Padang State University.Keywords: grade point average, micro teaching, practice of field experience (pfe), pedagogical competence